Coordinating online health communities for cognitive and affective value creation - Van Oerle, Sarah; Mahr, Dominik; Lievens, Annouk (International journal of service industry management, 2016)
Purpose – The purpose of this paper is to develop a framework investigating patterns of online health communities. In particular, the study draws on coordination theory to identify four community configurations. Their distinct features determine communities’ capacity to internalize and externalize knowledge, which ultimately determines their value creation in a service context. Design/methodology/approach – The authors apply qualitative and quantitative techniques to detect similarities and differences in a sample of 50 online health communities. A categorical principal component analysis combined with cluster analysis reveals four distinct community configurations. Findings – The analysis reveals differences in the degrees of cognitive and affective value creation, the types of community activities, the involved patients, professionals, and other stakeholders; and the levels of data disclosure by community members. Four community configurations emerge: basic information provider, advanced patient knowledge aggregator, systematic networked innovator, and uncomplicated idea sharer. Research limitations/implications – The findings show that communities can be categorized along two knowledge creation dimensions: knowledge externalization and knowledge internalization. While, previous research remained inconclusive regarding the synergistic or conflicting nature of cognitive and affective value creation, the findings demonstrate that cognitive value creation is an enabler for affective value creation. The emerging configurations offer a classification scheme for online communities and a basis for interpreting findings of future services research in the context of online health communities. Originality/value – This research combines coordination theory with healthcare, service, and knowledge creation literature to provide a fine-grained picture of the components of online health communities. Thereby, inherent trade-offs and conflicts that characterize the components of coordination theory are investigated.